ANALISIS PENGARUH FASILITAS, LOKASI, DAN HARGA TERHADAP KEPUTUSAN BERKUNJUNG KE OBJEK WISATA DEPATI COFFEE KOTA SUNGAI PENUH - Anggia Ayu Lestari; Kasman Karimi; Hamsiah Hamsiah (Jurnal Ekonomi Sakti, 2023)
This research aims to measure and analyze facilities, location and prices on the decision to visit the Depati Coffee tourist attraction in the city of Sungai Banyak. This type of research is descriptive research with a quantitative approach. The population used in this research is tourists at the Depati Coffee tourist attraction in Sungai Full City. Data collection was carried out using a questionnaire with a sample size of 80 respondents who visited the Depati Coffee Tourist Attraction, Sungai Full City. This research method uses a non-probability sampling technique with an accidental sampling technique. The data obtained from the questionnaire was then processed and analyzed using multiple linear regression analysis via SPSS software. The results of the research show that there is a significant and positive influence between Facilities on the Decision to Visit the Depati Coffee Tourist Attraction, Sungai Full City. on the decision to revisit the Depati Coffee tourist attraction, Sungai Full City and there is a significant and positive influence between Facilities, Location and Price on the decision to revisit the Depati Coffee tourist attraction, Sungai Full City.